One-pot Rh, P-containing carbon electrospun fibers catalysts for fixed-bed hydroformylation of propylene - Rodríguez-Cano, M. A.; García-Rollán, Miguel; Valero-Romero, María José; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (My University, 2025)
Hydroformylation is the largest homogeneous catalytic industrial process. The hydroformylation of propene to linear-butaldehyde is especially attractive due to the use of linear-butaldehyde as the starting material for the production of 2-ethylhexanol, which is the most important plasticizer alcohol in use. Nevertheless, their practical applications have been limited given that the most effective catalysts are homogeneous transition metal complexes, based on rhodium or cobalt, requiring industrially complicated catalyst-product separation steps. In this sense, the preparation of heterogeneous catalysts for hydroformylation would avoid these difficulties of separation, making heterogeneous hydroformylation reactions more economical and environmentally friendly. The present work focuses on the synthesis of electrospun Rh and P-containing carbon fibers catalysts, using lignin as carbon precursor, a low-cost co-product of the paper making industry, for the hydroformylation of propylene in a fixed-bed reactor.
Keywords: Catalizadores; Hydroformylation; Electrospun fibers; Propylene